VCAM-1-targeted magnetic resonance imaging reveals subclinical disease in a mouse model of multiple sclerosis. - Serres, S; Mardiguian, S; Campbell, S; McAteer, M; Akhtar, A; Krapitchev, A; Choudhury, R; Anthony, D; Sibson, N (2011)
Diagnosis of multiple sclerosis (MS) currently requires lesion identification by gadolinium (Gd)-enhanced or T(2)-weighted magnetic resonance imaging (MRI). However, these methods only identify late-stage pathology associated with blood-brain barrier breakdown. There is a growing belief that more widespread, but currently undetectable, pathology is present in the MS brain. We have previously demonstrated that an anti-VCAM-1 antibody conjugated to microparticles of iron oxide (VCAM-MPIO) enables in vivo detection of VCAM-1 by MRI. Here, in an experimental autoimmune encephalomyelitis (EAE) mouse model of MS, we have shown that presymptomatic lesions can be quantified using VCAM-MPIO when they are undetectable by Gd-enhancing MRI. Moreover, in symptomatic animals VCAM-MPIO binding was present in all regions showing Gd-DTPA enhancement and also in areas of no Gd-DTPA enhancement, which were confirmed histologically to be regions of leukocyte infiltration. VCAM-MPIO binding correlated significantly with increasing disability. Negligible MPIO-induced contrast was found in either EAE animals injected with an equivalent nontargeted contrast agent (IgG-MPIO) or in control animals injected with the VCAM-MPIO. These findings describe a highly sensitive molecular imaging tool that may enable detection of currently invisible pathology in MS, thus accelerating diagnosis, guiding treatment, and enabling quantitative disease assessment.